Drop-weight impact test on laminated composite plate of flax (Linum usitatissimum) using rice husk ash from paddy (Oryza sativa) as a natural binder - Yaakob, Mohd Saffuan; Zainal Abidin, Nur Amirah; Abdullah, Mohd Na'im; Muda, Mohd Khairul Hafiz; Mustapha, Faizal (Universiti Putra Malaysia Press, 2017)
Composite structures and materials are used in aerospace, marine and automotive applications due to their light weight characteristics. By using rice husk ash (RHA) as natural binder to replace epoxy resin, it improves the characteristic of the composite laminated structure. Rice husk has become an important ingredient in silica, silicon carbide, and silicon nitride because of its high a silicon content. This paper evaluates the performance of laminated composite plate in a drop-weight impact testing. Two plates are attached to the test rig in the particular desired impact orientation. The main advantages of this process are the plates provide more realistic drop-weight impact and data. Data from the impact test was collected and analysed to evaluate the material properties of epoxy resin and RHA. Results show RHA's energy absorption is better and it has more deformation to prevent structure failures compared with epoxy resin. This paper aims to evaluate the application of RHA as a geopolymer binder and flax fibre as an alternative material to glass fibre in the composites industry.